PERCEPTION OF TRAINING PARTICIPANTS ON GOOGLE SITES MEDIA IN LEARNING OF NATURAL SCIENCES - Waluyo, Joko; Siregar, Tiurlina; Hotlan Samosir (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2022)
The purpose of this study was to determine the trainees' perceptions of the use of google sites in learning Natural Sciences. This study uses a survey method approach with a descriptive nature which aims to describe the circumstances or phenomena that occur. The data collection technique used is a questionnaire (questionnaire), which is a data collection technique carried out by giving a set of questions or a written statement to the respondent. The results of the study indicate that multimedia-based learning media training with google sites is very necessary for participants in online learning and is useful for participants to provide subject matter to students because the conten to ngoogle sites can be adapted to the needs of the learning process